A modelagem molecular da proteína pha-like de Acacia Farnesiana revela mecanismo anti-inflamatório - Abrantes, Vanessa Erika Ferreira (2013)
Lectins are proteins or glycoproteins of non-immune origin that have at least one non-catalytic site which binds reversibly to carbohydrates and glycoconjugates, which makes them ideal models for studies of cell-cell interactions and cell-virus, being good models for the design of new drugs. Some carbohydrate-binding proteins resembling the lectins but with some structural and functional differences, that exclude of this group. The Fabaceae Acacia farnesiana has in its seeds an agglutinin chitin-binding (AFAL), classified as PHA-like1. Its standard chromatographic revealed time-dependent oligomerization. This dynamic behavior complicates the protein crystallization and determining of the three dimensional structure. To better understand the structure-function relationship, this study aimed to examine AFAL anti-inflammatory activity through structural comparison with legume lectins. For both, it was the molecular modeling and docking with a glycan and carrageenan. AFAL model is folded as a β sandwich, which differs from the template used (Pisum sativum lectin) in loop regions, number of β-sheets and carbohydrate site. The docking showed that the protein binds to the carrageenan and glycan at different sites, which can be explained by absence of the sixth β-sheet (frontal β-sheets) and two β-sheets in posterior region. The A. farnesiana agglutinin can inhibit carrageenan induced inflammation due binding it, preventing its entrance into the cell and triggers the inflammatory process reactions.